MYCROBIOTA FEATURES OF THE OBJECTS IN THE ONCOLOGY HOSPITAL ENVIRONMENT - Чарушина, Ирина Петровна; Фельдблюм, Ирина Викторовна; Коза, Наталья Михайловна; Александрова, Галина Арсентьевна; Баландина, Светлана Юрьевна (Medicine in Kuzbass, 2016)
Objective – to study the mycrobiota of the objects in the environment of the Radiology Department of the Perm Regional Oncology Hospital for adult patients. Materials and methods. The objects for microbiological examination were indoor air, the items of general and special medical equipment, the hands of the staff and patients, and sanitary equipment. The total number of samples was 63, including 12 air samples and 51 swabs from the objects in the hospital environment. Results. The high level of contamination of the Oncology Hospital environment by micromycetes was identified. The amount of positive samples was 90,5 ± 3,6 %. Fungi were detected in 100 % of air samples. Almost half of them were Penicillium species (49,7 %), the percentage of Aspergillus was 29,1 %. The intensity of contamination of various premises in the Radiology Department of the Oncology Hospital by fungi ranged from 50,6 ± 25,5 CFU/m3 to 2,0 ± 0,9 CFU/m3. However, no significant differences in the intensity of units contamination were revealed (t = 1,9; p > 0,05). The average «fungal load» was 19,4 ± 7,2 CFU/m3. The prevalence of yeast fungi was detected in swabs from the objects of the hospital environment. The highest contamination was found on the ventilation grates (6812,0 ± 1394,0 CFU/dm2) and the bedside tables (2427,0 ± 129,3 CFU/dm2). Conclusions. A high level of contamination of the environment of the Radiology Department of the Oncology Hospital by micromycetes was identified. Fungi of Aspergillus and Penicillium species prevailed in the air. The intensity of contamination did not exceed the threshold value. Yeast fungi prevailed in swabs from objects of the environment. The most contaminated were ventilation grates in the wards, bedside tables and patients’ hands. The intensity of contamination of the objects in the hospital environment by micromycetes does not depend on the intended usage of the premises in the hospital and duration of hospital stay of oncology patients.